Development of a Regional Power Market in the Greater Mekong Sub-Region : Compatibility of Regulatory Systems and Pricing Principles - Vernstrom, Robert (World Bank, Washington, DC, 2014)
A 1999 study by the Bank, which summarized the unprecedented opportunity for economic, and environmental benefits for individual countries, and the entire Greater Mekong Sub-region (GMS) associated with cross-border power trade, concluded that a full trade scenario, could yield significant savings over the next two decades, even before quantifying substantial environmental benefits. Based on these conclusions, GMS member countries were surveyed (attached as an appendix), and, this report compares the status of institutional/regulatory, and commercial policies across the region, to provide background information. Specifically, the focus is on the compatibility of national regulatory systems, especially for wheeling; the compatibility of pricing principles at both production, and transmission; and, the potential barriers to enhanced trade, which are revealed in this review. Section 2 provides a brief review of on-going reforms in member countries. Section 3 compares progress with respect to key regulatory, and commercial issues (particularly pricing) most critical to power trade, noting barriers to expanded power trade revealed through the country comparisons.